“Evaluación de la eficacia del paquete de estrategias mip propuesto por el proyecto amigo para el manejo de plagas en chocho (lupinus mutabilis sweet) en la parroquia Guaytacama, provincia de Cotopaxi 2022-2023” - Simbaña Quispe, Dilan Joel (2023)
The investigation was made in the Guaytacama parish, Cotopaxi province, to evaluate the effectiveness of the alternatives proposed by the AMIGO project in the control of pests in the cultivation of chochos ( Lupinus Mutabilis Sweet) with the implementation of integrated pest management: chemical, organic and traditional; this was done with applications of different products; In the organic field, products recommended by the AMIGO project based on organic products were applied, in chemical management synthetic products from local markets and farmer management without any type of product: The type of research that was managed was quantitative, since it worked with three units, the technique that was used was field observation, since the three strategies were implemented in the farmer´s land. The management was carried out for each technique and trough observation, the data was obtained for analysis; the data obtained each month were analyzed in Excel and Jamovi to obtain graphs and their respective analysis; It was observed that the incidence and severity one month after germination was incidence: 58% and severity: 44%, chemical management incidence: 30% and severity: 28% and traditional management incidence: 72% and severity: 49%; where it was observed that chemical management had better results in the efficacy in controlling the pests that attack the chocho, followed by organic management with encouraging results without such a marked difference from chemical management; in costs, organic management cost $175.92, chemical management $160.13 and traditional management $125.01; This analysis indicated that chemical management presented greater profitability, however, the environmental consequences are a factor to take into account; With this investigation, it was understood that there is still a difference between chemical and organic management in pest control, but without being so marked, it is necessary to continue with this type of investigation in order to restore the ecosystem of the place and give better results, alternatives to farmers.